A Comprehensive Theoretical Framework for Enhancing English Listening and Speaking Skills - Almuwaizri, Reem Mubarak (Journal of Educational Research and Policies, 2026)
This study examines the fundamental roles of listening and speaking in acquiring English as a Second Language (ESL) and English as a Foreign Language (EFL). Reviewing key theories and practical strategies, it identifies effective approaches to training these skills and discuss challenges learners face. The paper proposes solutions to enhance linguistic performance, aiming to contribute to improved educational practices in diverse language - learning contexts.